Excessive judicialization in social security: risks to fundamental rights and the role of the Judiciary as an agent of transformation (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article analyzes the phenomenon of excessive judicialization of social security claims in Brazil and its effects on the social protection system and fundamental rights. The main objective is to demonstrate how this scenario has overloaded the Judiciary, distorted the administrative function of the National Institute of Social Security (INSS), and undermined the enforcement of constitutionally guaranteed rights, while proposing alternatives to reduce litigation and strengthen administrative resolution. The methodology adopted is empirical-analytical, based on the analysis of data extracted from the INSS Panel of the National Council of Justice and supported by a specialized literature review. The study is structured into three axes: the presentation and interpretation of data on case volume, processing time, and conciliation rates; a critical analysis of the impacts of judicialization on fundamental rights; and the proposal of institutional measures to reverse this trend. The results show that judicialization, rather than ensuring access to justice, exposes structural deficiencies in the social security model and reinforces inequalities, calling for the adoption of integrated and preventive solutions.
Keywords: social security judicialization; fundamental rights; INSS; administrative efficiency; public policies